Counterparty credit risk, collateral and funding : with pricing cases for all asset classes - Brigo, Damiano, 1966-; Morini, Massimo; Pallavicini, Andrea (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
The book's content is focused on rigorous and advanced quantitative methods for the pricing and hedging of counterparty credit and funding risk. The new general theory that is required for this methodology is developed from scratch, leading to a consistent and comprehensive framework for counterparty credit and funding risk, inclusive of collateral, netting rules, possible debit valuation adjustments, re-hypothecation and closeout rules. The book however also looks at quite practical problems, linking particular models to particular'concrete' financial situations across asset classes, incl.
3.3.4 The Cox-Ingersoll-Ross Model (CIR) Short-Rate Model for r3.3.5 Time-Inhomogeneous Case: CIR++ Model; 3.3.6 Stochastic Diffusion Intensity is Not Enough: Adding Jumps. The JCIR(++) Model; 3.3.7 The Jump-Diffusion CIR Model (JCIR); 3.3.8 Market Incompleteness and Default Unpredictability; 3.3.9 Further Models; 3.4 Intensity Models: The Multiname Picture; 3.4.1 Choice of Variables for the Dependence Structure; 3.4.2 Firm Value Models?; 3.4.3 Copula Functions; 3.4.4 Copula Calibration, CDOs and Criticism of Copula Functions; PART II PRICING COUNTERPARTY RISK: UNILATERAL CVA.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance -- Mathematical models; Credit -- Mathematical models; Credit derivatives -- Mathematical models; Financial risk -- Mathematical models; BUSINESS & ECONOMICS -- Finance; Electronic books; Electronic books; Electronic books